2013
DOI: 10.1074/jbc.m113.471045
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell Activation Results in Extracellular Signal-regulated Kinase (ERK)-Calcineurin-dependent Exposure of Tn Antigen on the Cell Surface and Binding of the Macrophage Galactose-type Lectin (MGL)*

Abstract: Background: The C-type lectin macrophage galactose-type lectin (MGL) specifically dampens effector T cell function. Results: Activation through the ERK and calcineurin pathways leads to dramatic changes in T cell surface glycosylation. Conclusion: MGL-binding glycans are expressed only on recently activated T cells. Significance: This study provides mechanistic insight into the signaling pathways that regulate T cell surface glycosylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Comelli E.M. et al reported that the activation of murine T cells lead to a marked decrease of N-glycans carrying NeuAcα2,6Gal and the increase of O-glycans carrying the disaccharide Galβ1,3GalNAc on the cell surface 37. Similarly, van Vliet et al showed that the activation of human T cells via CD3/CD28 was accompanied by an increase in the expression of Galβ1,3GalNAc on the cell surface 38. We reported in this study direct visualization of a moesin-like protein on the activated CD4 + T cell surface.…”
Section: Discussionmentioning
confidence: 97%
“…Comelli E.M. et al reported that the activation of murine T cells lead to a marked decrease of N-glycans carrying NeuAcα2,6Gal and the increase of O-glycans carrying the disaccharide Galβ1,3GalNAc on the cell surface 37. Similarly, van Vliet et al showed that the activation of human T cells via CD3/CD28 was accompanied by an increase in the expression of Galβ1,3GalNAc on the cell surface 38. We reported in this study direct visualization of a moesin-like protein on the activated CD4 + T cell surface.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Tn antigen presentation to T cells has been found to be preferentially done through the binding to C‐type macrophage galactose‐type lectin. This leads to a subsequent downstream activation of the ERK‐calcineurin axis and downregulation of C1GALT1C1 expression . Upper respiratory tract infections and tonsillitis are also among the clinical manifestations seen in IgAN patients.…”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 99%
“…The role of Tn antigen in the development of cancer remains unclear. Several studies have reported that Tn antigen is bound by the C‐type macrophage galactose binding lectin (MGL) in situ in colorectal tumors . MGL is expressed in dendritic cells and macrophages .…”
Section: Relationship Between Tn Antigen and Tumor Cellsmentioning
confidence: 99%